PENGEMBANGAN ALAT PERMAINAN EDUKATIF FAKTA DASAR PENJUMLAHAN BILANGAN (1-10) PADA ANAK KELOMPOK B - Ayu soraya; Syafdaningsih syafar; hasmalena hasmalena (Tumbuh Kembang: Kajian Teori dan Pembelajaran PAUD, 2019)
This study aims to development of basic facts educative game of number (1-10) in group B in children that are valid and practical by used combination of Ronwtree development models and Tessmer evaluations. The Rowntree development model consistsed of three stages, namely the analysis, development, and evaluation stages. The evaluation used is Tessmer formative evaluation, consis stages of self evaluation, expert review, one-to-one evaluation, small group evaluation. The expert review results obtained an average percentage of the assessment results from educational tools on the basic facts of adding numbers (1-10) by media and material experts. The obtained percentage 93% with very valid categories which included content validity and constructs. The mean, the basic fact game tool corresponds to the material about the basic facts of addition, for example for the basic facts of numbers 10 is 1 + 9, 2 + 8, 3 + 7 and so on in other words the basic fact of addition 10 is the sum of 10 results. The results of the one-to-one and small group evaluation stages were obtained percentage of 94,5% with a very practical category, that is mean the basic fact game tools were in accordance with the requirements: easy to use, interested, and meaningful for children. However, the basic fact game tool still experiences a deficiency of 7% because the colors used in the game device must contrast with the color numbers so that the numbers are more clearly visible,while practically still found deficiency of 5,5% because the game equipment material used is 5 ml plywood which is felt very hard for the child For this reason, it is recommended that the next researcher use the plywood 3 ml and increase the size of the number card from 5 cm x 3.5 cm before.